2021
DOI: 10.1093/mnras/stab2201
|View full text |Cite
|
Sign up to set email alerts
|

Towards robust determination of non-parametric morphologies in marginal astronomical data: resolving uncertainties with cosmological hydrodynamical simulations

Abstract: Quantitative morphologies, such as asymmetry and concentration, have long been used as an effective way to assess the distribution of galaxy starlight in large samples. Application of such quantitative indicators to other data products could provide a tool capable of capturing the 2-dimensional distribution of a range of galactic properties, such as stellar mass or star-formation rate maps. In this work, we utilize galaxies from the Illustris and IllustrisTNG simulations to assess the applicability of concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 88 publications
3
14
0
Order By: Relevance
“…The results are not sensitive to redshift. The typical half-light radius of our sources is ∼2.5 times the PSF size, and we have verified that no strong dependence on redshift can be discerned (Figure 9), consistent with the tests performed by Thorp et al (2021) to evaluate the effect of resolution on asymmetry measurements.…”
Section: Comparing the Asymmetries Of Star-forming Galaxies And Agnssupporting
confidence: 87%
See 3 more Smart Citations
“…The results are not sensitive to redshift. The typical half-light radius of our sources is ∼2.5 times the PSF size, and we have verified that no strong dependence on redshift can be discerned (Figure 9), consistent with the tests performed by Thorp et al (2021) to evaluate the effect of resolution on asymmetry measurements.…”
Section: Comparing the Asymmetries Of Star-forming Galaxies And Agnssupporting
confidence: 87%
“…This confirms that the uncertainty introduced by the background primarily contributes to the error budget of our A CAS and A outer measurements of the SFGs. Previous studies (e.g., Conselice et al 2000;Thorp et al 2021) found that the asymmetry is dominated by the background noise if the source S/N is below 100. With a typical S/N  100, our galaxies should have reliable asymmetry measurements.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…signal-to-noise) and choices in preprocessing, models, and optimization routines (e.g. Simard et al 2011;Häußler et al 2013;Mendel et al 2014;Bernardi et al 2014;Meert et al 2015;Bottrell et al 2019a;Thorp et al 2021). Therefore, the second key advantage of: (a) accurately incorporating observational effects (realism) into synthetic observables and (b) using the same tools to analyze the observations and simulations, is that any divergences between recovered properties will be due to their intrinsic differences and not caused by e.g.…”
Section: Introductionmentioning
confidence: 99%